Leveraging visual-spatial abilities to unlock speech: an arts-based interdisciplinary approach to promoting inclusion and equity for children with Autism / Muhamad Hafiz Hassan ... [et al.] - Hassan, Muhamad Hafiz; Wardi, Rainal Hidayat; Abdullah, Mohamad Hariri; Isa, Badrul (Universiti Teknologi MARA, Perak, 2024)
This paper investigates the relationship between visual-spatial abilities, cognitive factors, affective factors, and speech fluency achievement in children with Autism Spectrum Disorder (ASD). ASD impacts communication, behavior, and thinking. Children with ASD often exhibit speech fluency difficulties, which can inhibit academic success. However, individuals with ASD possess strong visual-spatial abilities for processing visual information. This study hypothesized that visual-spatial abilities influence speech fluency through cognitive factors (prior knowledge, executive functions) and affective factors (self-efficacy, attitude). A conceptual framework integrated Novak’s Meaningful Learning Model examining relationships between cognitive, affective, and achievement factors. A quantitative methodology utilized questionnaires to collect data for statistical analysis. Results revealed positive, significant effects of cognitive and affective factors on speech fluency. Mediation analysis found partial mediator effects for prior knowledge, attitude, and executive functions between visual-spatial abilities and speech fluency. Findings supported an integrated Visual-Spatial Mediated Model of Speech Fluency in ASD Children (i-VSM). This model can guide interventions to improve speech and language outcomes for children with ASD, supporting their educational development and success. Findings have implications for supporting the UN Sustainable Development Goals on quality education and reduced inequalities for disadvantaged children.